A Simplified method for calculating warping constant for lipped I-beam with Trapezoidal corrugation in web - Kumar, G. Arun; Sukumar, S. (Journal of Structural Engineering, 2024)
The lateral torsional buckling strength is more dominant than the flexural strength in thin walled open flexure member. To find lateral torsional buckling strength, warping constant is required. The calculation of warping constant for an open thin-walled section is a tedious and difficult task, thus presenting a challenge to routine design. In open section like lipped I-beam with trapezoidal corrugation in the web, the cross-section profile varies along the span of the beam. Since the cross-section of trapezoidal corrugation varies along the longitudinal direction of the beam, it is difficult to find warping constant. In this paper, a simplified method for locating shear center and calculating the warping constant of lipped I-beam with trapezoidal corrugation in web is proposed. Using this, lateral torsional buckling strength can be calculated easily. A series of finite element analyses under uniform bending are conducted and their results are compared with those of the proposed method. An experimental investigation has also been carried out for the above analyzed beam under two point loading and the warping constant is evaluated to validate the proposed method.